Social validation of an online tool to support transitions to primary school for children with autism. (October 2019) - Sulek, Rhylee; Trembath, David; Paynter, Jessica; Keen, Deb
Highlights: Online prototype to supporting transition found to be socially valid. Stakeholders in transitions to school highlighted potential value of approach. Stakeholders also highlighted acceptability and appropriateness of online approach. Abstract: Background: Successful transitions into primary school for children with autism relies on both the readiness of children to attend school and the readiness of schools and teachers to support students with additional needs. There is evidence that (a) connections between education settings, (b) teachers' access to quality resources, and (c) support from other professionals, have the potential to contribute to successful transitions (see Hess et al., 2008; Jackson & Bruegmann, 2009; Pianta & Kraft-Sayre, 2003), however, the extent to which they are present is varied. This study examined the views of parents, teachers, heads of special education, and inclusive support staff regarding the social validity of harnessing these three factors in an online tool to support transitions to primary school. Method: Using a qualitative approach, 21 stakeholders participated in interviews in which they (a) shared their views regarding the relevance of the three factors and (b) considered the application of these factors within a prototype online tool. Results: The 'Potential Value' of the factors was explored, highlighting opportunities for the prototype online tool to increase the capacity of teachers working with students with autism while providing access to information and professional support. While the combination of factors, packaged as an online tool, was 'Acceptable and Appropriate' participants also emphasized that in development of any new tool there is a need to be conscious of, and not undermine, existing processes and systems. Conclusions: These findings highlight the potential value and appropriateness of combining and presenting the identified factors in tools to support transitions to primary school for students with autism.